The First COL4A5 Exon 41A Glycine Substitution in a Family With Alport Syndrome - Wang, Fang; Zhao, Dan; Ding, Jie; Li, Xuejuan (Frontiers in Pediatrics, 2020)
Background: X-linked Alport syndrome is caused by mutations in the COL4A5 gene, which encodes the a5(IV) chain. No mutations were detected in COL4A5 exons 41A and 41B. Materials and Methods: A Chinese family with suspected Alport syndrome was enrolled in the present study to establish a precise diagnosis. The indirect immunofluorescence method was used for analysis of distribution of a1 (IV) and a5 (IV) chains in the epidermal basement membrane from the father of the proband. The entire coding region of COL4A5 mRNA from the proband’s father cultured skin fibroblasts was analyzed by using reverse-transcription polymerase chain reaction (RT–PCR) and direct sequencing, and genomic DNA was analyzed by using PCR and direct sequencing. To examine whether the alternatively COL4A5 mRNA transcripts existed in cultured skin fibroblasts, a fragment of COL4A5 cDNA, including exons 41A, 41B and partial sequences of exons 41 and 42 was analyzed by RT–PCR and GeneScan. Results: Negative a5(IV) chain staining in the epidermal basement membrane was detected in the female proband’s father who presented with hematuria, proteinuria and renal dysfunction. Sequencing analysis demonstrated that the proband’s father had a novel variant c.3791G>A [p. (Gly1264Asp)] in COL4A5 exon 41A detected at the mRNA and genomic DNA levels, and the variant segregated with disease in the family. According to the phenotype and American College of Medical Genetics and Genomics guideline, this variant was considered clinically pathogenic. The GeneScan analysis showed three COL4A5 mRNA transcripts expressed in the cultured skin fibroblasts of the proband’s father and two normal males, and variation could be seen in the amounts of amplified isoforms. Conclusions: we have identified a family with a glycine substitution in COL4A5 exon 41A for the first time, which extends the phenotypic and mutational spectrum of X-linked Alport syndrome. In addition, skin tissue has three distinct COL4A5 transcripts with a diversity of expression.